Beyond Temperature Glide: The Compressor is Key to Realizing Benefits of Zeotropic Mixtures in Heat Pumps. Issue 4 (18th February 2021) - Roskosch, Dennis; Venzik, Valerius; Schilling, Johannes; Bardow, André; Atakan, Burak
Abstract : Zeotropic mixtures are widely discussed as alternative refrigerants for vapor‐compression cooling appliances and heat pumps. Mixtures can increase efficiency due to their nonisothermal phase change. In theoretical studies, zeotropic mixtures show significant benefits for efficiency if the temperature glide of the mixture matches the temperature change in the heat transfer fluids. Such large benefits have never been observed in experiments. First, this article clarifies the gap between simulations and experiments. Second, it is shown how zeotropic mixtures could increase efficiency in real plants. The analysis is based on experimental results from a heat pump with three zeotropic mixtures and on theoretical studies that also include a physical compressor model. The compressor performance is shown to depend strongly on composition. Therefore, the compressor efficiency is the key parameter for large benefits of zeotropic mixtures beyond well‐matching temperature glides. Based on these findings, a fluid database is screened for fluids with well‐matching temperature glides and high compressor efficiencies, utilizing a physical compressor model. As a result of the screening, the zeotropic mixture R152a/R32 is identified. The corresponding simulations show that zeotropic mixtures can achieve large benefits in heat pump efficiency if the pure components have similar and high compressor efficiencies. Abstract : How to select zeotropic mixtures to increase heat pump efficiency? Why has a well‐matching temperature glide not been sufficient to realize efficiency gains in practice? This article aims to provide answers by showing the mixture impact on the compressor and presenting a mixture selection criterion beyond the temperature glide.